Peningkatan Kemampuan Ketrampilan Sosial Pasien Gangguan Jiwa di Masyarakat dengan Terapi Hortikultura - Widyo Subagyo; Dyah Wahyuningsih; Mukhadiono Mukhadiono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the effect of the development of horticultural therapy to improve the social skills of mental disorders patients in the community. This research's method is quantitative research with a pre-posttest queasy experimental research design with a control group. The study results the social skills score before and after treatment in the intervention group given horticultural therapy was marked with a p-value of 0.01 (<0.05). In conclusion, there is a significant difference in the mean difference in social skills scores between the intervention and control groups. Keywords: Mental Disorders, Social Skills, Horticultural Therapy